Psychological security and its relationship to fear of academic failure among university students (Journal of the College of Basic Education, 2025)
University education has a prominent position among other stages of education due to the pioneering role played by this type of movement of civilizational growth for societies. University students are sometimes exposed to problems and crises in their academic life. Psychological security is one of the basic needs necessary for the healthy psychological growth of each individual. When a university student feels a lack of psychological security within the university campus, this leads him to feel insecure and unstable in his studies, which affects his ability to achieve academic achievement and thus his feeling of poor compatibility and even to his feeling of academic failure. (Girgis, 2000, p. 55) It also leads to the emergence of some psychological disorders and diseases such as fear, anxiety and depression. It shows feelings of lack of confidence in the world around him, which leads to isolation and distancing from his group. On the other hand, the loss of a sense of psychological security may make students feel fear and a sense of deficiency and mental health disorder and may lead to hatred for the source of the loss. (Al-Khalidi, 1990, p. 75)Fear of academic failure is a problem for many students at all different educational levels, as the person who fears failure shows some symptoms of tension and anxiety, and hinders the educational process in achieving its goals, as it occupies a prominent place among those working in the field of educational, psychological, social and biological sciences, and is even the most important problem that worries educators and students alike (Khairallah, 1981: 151). And the fear of academic failure affects the process of self-realization and mutual relationships with others, and therefore special attention should be given by educational institutions, in addition to general attention from society (Jedka Rensef, 2000: 89 p.). Therefore, this problem greatly affects the student's morals and the moral system of society. Studies have indicated that those who fail academically more than once, those who repeated the year for the second time, and those who were looking forward to academic success but failed are more likely to feel academic incompetence and that they are not worthy of success. Therefore, they will work at a level much lower than their actual level due to their falling into internal conflicts that dissipate their energies and prevent them from organizing their thinking. They show great sensitivity and complex expectations for any form of criticism and evaluation from others (Mahdi, 1973, 248 p.). The fear of academic failure is directly exposed to the individual in the academic field, which makes students who feel this fear weak, unstable, and depressed (Mohammed, 2008: 81). Therefore, the problem of the current research stems from the following question: Is there a relationship between psychological security and fear of academic failure among university students?